Comparison Between Serum Electrolyte Levels in Full-Term Healthy Neonates Versus Neonates with Hypoxic Ischemic Encephalopathy: Serum Electrolyte Levels in Healthy Neonates Versus Neonates with HIE - Iftikhar, Kiran; Ijaz, Samar Fatima; Husnain, Muhammad (Pakistan Journal of Health Sciences, 2026)
Hypoxic ischemic encephalopathy (HIE) is a major cause of neonatal mortality and neurological disability. Hypoxia leads to multisystem involvement, causing electrolyte disturbances such as hyponatremia, hyperkalemia, and hypocalcemia, causing adverse clinical outcomes. Most studies assess these abnormalities after 24 hours of life. Detection within the first 12 hours may help reduce complications and long-term disability. Objectives: To compare serum sodium, potassium, and calcium levels in full-term healthy neonates versus those with HIE. Methods: This cross-sectional study was conducted at King Edward Medical University from June 2025 to November 2025 (IRB letter no. 512/RC/KEMU). Patients presenting to Mayo hospital over six months period were evaluated to determine the frequency of hypoxic-ischemic encephalopathy (HIE). After taking informed consent, 228 eligible subjects were identified, comprising 114 HIE and 114 non-HIE patients. Serum sodium, calcium, and potassium levels were measured within the first 12 hours of life and were compared between the two groups. Data were analyzed using SPSS version 27.0, and an independent t-test and Chi-square test were applied with a p-value <0.050. Results: The frequency of neonates diagnosed with HIE was 9.7%. Hyponatremia (32.3%), hyperkalemia (22.8%), and hypocalcemia (8.8%) were significantly more common in neonates with HIE. These differences were statistically significant (p<0.001). Conclusions: Compared to healthy neonates, neonates with HIE demonstrated significantly higher rates of electrolyte abnormalities. Identification of these electrolyte abnormalities is crucial, as timely detection and correction can play an important role in preventing further neurological damage, thereby enhancing clinical outcomes in affected neonates.